Identification of a Spotted Leaf Sheath Gene Involved in Early Senescence and Defense Response in Rice - Lee, Dongryung; Lee, Gileung; Kim, Backki; Jang, Su; Lee, Yunjoo; Yu, Yoye; Seo, Jeonghwan; Kim, Seongbeom; Lee, Yong-Hwan; Lee, Joohyun; Kim, Sunghan; Koh, Hee-Jong (Frontiers in Plant Science, 2018)
Lesion mimic mutants (LMMs) commonly exhibit spontaneous cell death similar to the hypersensitive defense response that occurs in plants in response to pathogen infection. Several lesion mimic mutants have been isolated and characterized, but their molecular mechanisms remain largely unknown. Here, a spotted leaf sheath (sles) mutant derived from japonica cultivar Koshihikari is described. The sles phenotype differed from that of other LMMs in that lesion mimic spots were observed on the leaf sheath rather than on leaves. The sles mutant displayed early senescence, as shown, by color loss in the mesophyll cells, a decrease in chlorophyll content, and upregulation of chlorophyll degradation-related and senescence-associated genes. ROS content was also elevated, corresponding to increased expression of genes encoding ROS-generating enzymes. Pathogenesis-related genes were also activated and showed improved resistance to pathogen infection on the leaf sheath. Genetic analysis revealed that the mutant phenotype was controlled by a single recessive nuclear gene. Genetic mapping and sequence analysis showed that a single nucleotide substitution in the sixth exon of LOC_Os07g25680 was responsible for the sles mutant phenotype and this was confirmed by T-DNA insertion line. Taken together, our results revealed that SLES was associated with the formation of lesion mimic spots on the leaf sheath resulting early senescence and defense responses. Further examination of SLES will facilitate a better understanding of the molecular mechanisms involved in ROS homeostasis and may also provide opportunities to improve pathogen resistance in rice.